Quality Physical Education Teaching: Be Prepared to Accept the Challenge Raised by the Proposed Educational Reform for the 21st Century: 優質學校體育敎學: 迎擊二十一世紀敎育改革藍圖的挑戰 - WONG, Arthur Chi Tak (Asian Journal of Physical Education & Recreation, 2000)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. School physical education is facing a lot of problems. One of these problems is a negative image that is gradually developing. Our pupils seem to dislike PE more and more. Lots of research has indicated that sports participation from the youth and adult populations are declining and that young people nowadays are not as fit as their counterparts before. This phenomenon could be accounted for, at least partly, by the quality and approach of implementation, of our curriculum. The author wishes to share with the audience some observations with reference to the recent proposals made in the Review of Education system: Framework for Education Reform - Learning for Life (Education commission, 1999). The reform proposal, seem to aim at making individual schools more accountable for their own education program and creating a more flexible and dynamic environment. It emphasizes life-long learning; proposes to demolish the murals that separate the schools from other social institutes and to alleviate the pressure and limitations in terms of time, facilities and equipment that constrain the curriculum. The proposals offer both challenges and opportunities to change the teaching of PE and have great bearings to our professional goals, curriculum content, pedagogy and assessment. Owing to time limitation it is difficult to offer a comprehensive view on all possibilities but an eclectic visit on some of the issues. 學校體育面對很多困難，其一為學校體育在學生心中的負面形象，正在慢慢形成，不喜歡體育課的學生多了。大量研究指出時下的青少年及成年人不積極參與運動，今天的青少年比過去的體弱。這一現象部分可能與現行的體育課程及其施行方法有關。筆者希望就「敎育制度檢討: 敎育改革建議 - 終身學習」(敎育統籌委員會，1999)提出的藍圖和讀者分享一些見聞。改革建議希望在一個更具彈性及動力的環境下建立一套問責制，它強調終身學習，並試圖把學校與社會其它機構的圍牆拆去，把學校課程從時間，空間，用具及設施等限制中解放出來。改革建議提出了挑戰及機會，對體育敎學的目的、內容、敎學方法及評估皆有啟示。基於時間及篇幅的限制，這裡未能照顧周全，只能探討其中一些問題。